Empowerment Strategy of Farmers through Biogas Utilization to Achieve Energy Self-Sufficiency Village - Nurtanti, Ina; Wijayanti, Desna Ayu (Bantara Journal of Animal Science, 2025)
The empowerment of livestock farmers through the utilization of cow manure biogas plays a crucial role in addressing environmental pollution and enhancing rural energy self-sufficiency. This study aims to analyze the empowerment strategy of farmer groups (KTT) in Sruni Village, Musuk District, Boyolali Regency, Central Java, Indonesia, through a participatory biogas utilization program. A survey method using Participatory Rural Appraisal (PRA) was employed with 45 respondents determined by census sampling. Data were collected through observation, interviews, and Focus Group Discussions (FGD), and analyzed using SWOT analysis. The results of the SWOT analysis indicate that internal strengths include the economic value of biogas, environmental benefits, and the availability of livestock waste, while weaknesses include a lack of skills, insufficient government support, and limited financial resources. External opportunities encompass potential for educational tourism, economic creativity development, and energy substitution. Threats include technical constraints such as installation damage and gas pressure hazards. Based on the SWOT matrix, the recommended strategies emphasize capacity building, technological improvements, strengthening farmer institutions, and promoting biogas as an alternative energy source. The recommended empowerment strategies involve enhancing farmer capacity, optimizing biogas management, improving installation technology, and promoting biogas as an alternative energy source. This study concludes that strategic empowerment interventions can significantly contribute to the realization of energy self-sufficient villages and circular rural economies.